Analysis of Human Resources Competency in Improving Employee Performance at Bank Woori Saudara KCP Sumedang - Sukmayadi Sukmayadi; Ading Rahman Sukmara (CV. Ulil Albab Corp, 2024)
This research aims to determine human resource competency in improving employee performance. The method used in this research is a qualitative method using data collection techniques through observation, interviews and documentation. Data obtained directly from informants, namely employees of Bank Woori Saudara KCP Sumedang. The sampling technique used was purposive sampling which was analyzed through dimensions and indicators. The results of the research show that human resource competency in improving employee performance carried out by Bank Woori Saudara KCP Sumedang is good, although in several indicators employee competency is still found to be optimal and needs to be improved again. Then it was also found that some employees were too focused on the target tasks given, without balancing it with their potential, which also had an impact on performance.